Teller Services Optimization Using Lean Service Approach at PT. ABC - Nur Rahmawati; Sumiati; M.Tutuk Safirin; Tranggono; Sinta Dewi (Future Science, 2023)
A bank can be considered good when it can satisfy its customers by providing excellent service and comfort. One of the banks facing challenges in this regard is PT. ABC Sidoarjo branch. This branch has only three teller services. In the queue, customers often feel uncomfortable, and bored, and their time is wasted waiting. This research aims to minimize waste to optimize the teller service queue. The research starts with data collection, distributing questionnaires, and analyzing data using Lean Service methodology. To visualize the value stream of business processes at PT. ABC, Value Stream Mapping (VSM) is used. Cash deposit activities contribute significantly to waste. Within the cash deposit service process, it was found that value-added activities account for 64%, necessary non-value-added activities for 29%, and non-value-added activities for 7%. The critical types of waste are waiting and unnecessary movement, each with a percentage of 24% and 22%, respectively. After the research and proposed improvements were implemented, After the improvement, the non-value-added activity decreased from the initial 900 seconds to 300 seconds, which represents a 66.7% reduction. As a result, customers no longer need to wait in line for an extended period.